ChemInform Abstract: Antimicrobial Treatment of Different Metal Oxide Nanoparticles: A Critical Review. Issue 25 (June 2016) - Parham, Shokoh; Wicaksono, Dedy H. B.; Bagherbaigi, Saeedeh; Lee, Siew Ling; Nur, Hadi
Abstract: Review: 136 refs.